A Study On the Use of Collocations in Business Class Learners - Suleman, Nazia; Deep, Sadia; Othman, Hussain; Ahmed, Ali; Abbas, Muhammad Zahid; Nawaz, Muhammad Zahid; Nazar, Uzma; Shaheen, Hina (Colombian Applied Linguistics Journal, 2020)
Previous studies have reported lack of collocational competence and difficulties among English as a second language (ESL) learners. However, collocation is crucial in second language acquisition. This research examined the receptive and productive knowledge of collocations among the business students of COMSATS University Islamabad Vehari Campus who studied ESL. It also investigated the gap in the use of collocations at a receptive and productive level. The sample included 61 males and 39 females out of the total sample size of 100. Employing a quantitative approach, we gathered the data through a questionnaire and two collocations tests, and we analysed them via SPSS version 20. The overall result of the collocation test indicated that 66.4% of the respondents had the correct answer at the receptive level compared with only 33.7% at the productive level. Moreover, the statistical result presented a great gap in the ability to utilise collocations at the productive and receptive levels. This result also affirmed that despite their ability to understand the collocations, the students had difficulties in identifying proper English collocations confidently. Local and native language experiences might be one of the reasons that caught the students from being more confident in identifying the English collocations.